The Effectiveness of Public Sector Governance at the Ministry of Health of the Republic of Indonesia - Andhika Yudha Pratama; Wita Juwita Ermawati; Gendut Suprayitno (Jurnal Indonesia Sosial Sains, 2024)
The rapid development of the times always demands changes in every sector, including in the scope of government. In running the government system, good public sector governance is needed, where its implementation is further developed through bureaucratic reform, which refers to Presidential Regulation Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010-2025. As one of the government agencies, the implementation of bureaucratic reform is carried out by the Ministry of Health of the Republic of Indonesia, one of which is realized through strengthening performance accountability, which refers to Presidential Regulation Number 29 of 2014 concerning the Performance Accountability System of Government Agencies. The results of the evaluation of the 2015-2022 Government Agency Performance Accountability assessment are always at the predicate of "BB" with a relatively stagnant value between >70-80 according to the 2015-2022 Government Agency Performance Accountability Evaluation Report of the Ministry of Health of the Republic of Indonesia. Therefore, this study aims to analyze the effectiveness of public sector governance in implementing the Government Agency Performance Accountability System at the Ministry of Health of the Republic of Indonesia. The population in this study is the State Civil Apparatus of the Ministry of Health of the Republic of Indonesia, and the sample selection uses non-probability sampling with a purposive sampling technique. The research was carried out qualitatively by adopting Duncan's theory of effectiveness in his book "Organizational Effectiveness," which consists of the dimensions of goal achievement, integration, and adaptation. The results of the study show that public sector governance in the implementation of the Government Agency Performance Accountability System at the Ministry of Health of the Republic of Indonesia, in general, has been running effectively from the dimension of measuring integration and adaptation, while when viewed from the dimension of measuring the achievement of goals is still not fully running effectively.